2002
DOI: 10.1038/sj.jhh.1001440
|View full text |Cite
|
Sign up to set email alerts
|

The reno-protective role of AT1-receptor blockers

Abstract: In the 1970s and 1980s it became evident that progression of renal disease and blood pressure are correlated. Subsequently, it was shown that antihypertensive treatment, especially with agents that block the renin-angiotensin system (RAS), could slow the progression of diabetic renal disease. Several studies, particularly with RAS blockers, have confirmed beneficial effects on urinary albumin excretion in patients with diabetes and microalbuminuria or proteinuria. There are good reasons to explore dual blockad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…However, a study on imidapril found no increase in reninangiotensin-aldosterone system blockade when dosages from 2.5 to 10 mg were compared (22). It is possible that alternative approaches to renin-angiotensin-aldosterone system blockade may be required (24). Such approaches may include the combination of ACE-I agents with angiotensin II receptor blockers (24 -26) or the use of aldosterone blockade agents such as spironolactone (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…However, a study on imidapril found no increase in reninangiotensin-aldosterone system blockade when dosages from 2.5 to 10 mg were compared (22). It is possible that alternative approaches to renin-angiotensin-aldosterone system blockade may be required (24). Such approaches may include the combination of ACE-I agents with angiotensin II receptor blockers (24 -26) or the use of aldosterone blockade agents such as spironolactone (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Studies in patients with type II diabetes, who are usually overweight, clearly indicate that ACE inhibitors and ANG II receptor antagonists slow progression of renal disease. 24,51 However, additional studies are needed in nondiabetic obese subjects to determine whether RAS blockers are more effective than other antihypertensive agents in reducing the risk of renal injury.…”
Section: Renin-angiotensin System Alters Renal Function and Increasesmentioning
confidence: 99%
“…In particular, the evidence that telmisartan has the same beneficial effect of vitamin C in improving the long-lasting effect of hyperglycemia, in our opinion, deserves attention. In fact, the effectiveness of a chronic long-term treatment with vitamin C is still an open debate (35), whereas telmisartan and other AT-1 receptor blockers are already widely used for the prevention of diabetes complications, particularly nephropathy (36). It seems reasonable to suggest that an AT-1 receptor blocker is a much better form of therapy than vitamin C because a recent study indicates that vitamin C intake increases mortality in postmenopausal women with type 2 diabetes (37).…”
Section: Ceriello and Associatesmentioning
confidence: 99%